1542 An Audit of Rates of Lynch Testing in Confirmed Colorectal Cancer Cases. (12th October 2021) - Cribb, E; Liccardo, F; Crisford, S; Pawa, N
Abstract: Introduction: 12% of cancers in the UK are colorectal in origin 1 with 1-3% secondary to genetic mismatch repair due to Lynch syndrome 2, for which the 2017 NICE guidance recommended that patients with colorectal cancer (CRC) be tested 3 . It increases the risk of developing other cancers such as endometrial, ovarian and small bowel 1, changes the oncological treatment offered to CRC patients 4, 5, and prompts investigation of their relatives for the condition. In this audit we assessed our rates of trust wide Lynch testing. Method: Patients with a diagnosis of CRC from 2017-2019 were identified from records held by our cancer services department. Histology results were obtained from an online results portal. Results: 345 were included in the analysis, 79% of which were tested for Lynch, with time taken from biopsy to results ranging from 2 to 276 days (average 45). 54% had results within 30 days, 34% between 30 and 90 days and 12% exceeded 90 days. There was no significant difference of Lynch testing rates between each year. The proportion of results returned within 30 days increased by year, with rates of 30% (2017), 55% (2018) and 71% (2019). The median days from biopsy to results also improved, from 39 to 28 and 16 days, respectively. Conclusions: Rates and efficiency of our screening for lynch syndrome need improvement to meet the target suggested by NICE. The impact of the recent centralisation our regions pathology department on Lynch testing service provision requires further investigation.